Gonococcal vaccines: Public health value and preferred product characteristics; report of a WHO global stakeholder consultation, January 2019. Issue 28 (9th June 2020) - Gottlieb, Sami L.; Ndowa, Francis; Hook, Edward W.; Deal, Carolyn; Bachmann, Laura; Abu-Raddad, Laith; Chen, Xiang-Sheng; Jerse, Ann; Low, Nicola; MacLennan, Calman A.; Petousis-Harris, Helen; Seib, Kate L.; et al.
Abstract: Renewed interest in developing vaccines against Neisseria gonorrhoeae has been sparked by the increasing threat of gonococcal antimicrobial resistance (AMR) and growing optimism that gonococcal vaccines are biologically feasible. Evidence suggests serogroup B Neisseria meningitidis vaccines might provide some cross-protection against N. gonorrhoeae, and new gonococcal vaccine candidates based on several approaches are currently in preclinical development. To further stimulate investment and accelerate development of gonococcal vaccines, greater understanding is needed regarding the overall value that gonococcal vaccines might have in addressing public health and societal goals in low-, middle-, and high-income country contexts and how future gonococcal vaccines might be accepted and used, if available. In January 2019, the World Health Organization (WHO) convened a multidisciplinary international group of experts to lay the groundwork for understanding the potential health, economic, and societal value of gonococcal vaccines and their likely acceptance and use, and for developing gonococcal vaccine preferred product characteristics (PPCs). WHO PPCs describe preferences for vaccine attributes that would help optimize vaccine value and use in meeting the global public health need. This paper describes the main discussion points and conclusions from the January 2019 meeting of experts. Participants emphasized the need for vaccines to control N. gonorrhoeae infections with the ultimate goals of preventing adverse sexual and reproductive health outcomes (e.g., infertility) and reducing the impact of gonococcal AMR. Meeting participants also discussed important PPC considerations (e.g., vaccine indications, target populations, and potential immunization strategies) and highlighted crucial research and data needs for guiding the value assessment and PPCs for gonococcal vaccines and advancing gonococcal vaccine development.